A Efektivitas Metode Ummi Dalam Mengatasi Kesulitan Membaca Huruf Hijaiyah di MTs Rahmat Sa’id Bongkot Peterongan Jombang: Efektivitas Metode Ummi Dalam Mengatasi Kesulitan Membaca Huruf Hijaiyah di MTs Rahmat Sa’id Bongkot Peterongan Jombang - Anjani Ichsan, Safira; Syamsuddin (Al Tadib : Jurnal Ilmu Pendidikan, 2025)
Methods with models teach fluency in reading the Koran without forgetting tajwid as a reference for justification starting from hijaiyah letters. Difficulty reading Hijaiyah Letters can sometimes be seen clearly in students. The focus set to be discussed this time is that the ummi method can overcome the difficulties of MTs Rahmat Sa'id Bongkot students in reading hijaiyah letters, so this research aims to reveal the results of learning the ummi method in overcoming difficulties in reading hiijaiyah letters. The procedure used is guided by the selection of qualitative as an appropriate method. The findings show that the ummi method is effective in overcoming difficulties in understanding hijaiyah letters at MTs Rahmat Sa'id Bongkot. easy, fun and heart touching is the motto as the right footing in this method. The existence of a motto that is embedded in this presentation makes it easier for students to overcome their difficulties in understanding the reading of hijaiyaah letters.